Evolution of artificial intelligence research in human resources - Jatoba, Mariana Namen (2020)
The objective of the article is to investigate the evolution of the application of Artificial Intelligence (AI) in the area of Human Resources (HR). It presents a panorama of the research that used AI in the area of HR, through the quantitative descriptive analysis of journals and proceedings, registered in the base of the Library of Online Knowledge (B-on), in the period between the years of 2000 and 2018. 32 research publications have been identified that address the application of Artificial Intelligence in the Human Resources area. As a didactic support and aiming to facilitate the understanding of the analysis, the period of the 18 years studied was divided into 3 time periods (First decade, Reduction Period and Period of Growth). The study also raised the distribution of AI application in HR topics and the incidence in each of these themes. As a result, it was concluded that there are few researches on AI applied to Human Resources and a dispersed use behaviour. It is expected that the 9 inferences about the results mentioned in this essay will elicit future studies.